Action Games as A Means of Harmonious Development of Children (Web of Teachers: Inderscience Research, 2023)
The article considers the role of outdoor games in optimizing the motor and mental activity of primary school children. The main methods, means and forms of introducing outdoor games into family pedagogy are described. This article will be of interest to parents, specialists of school, preschool institutions, social workers.